2016
DOI: 10.30638/eemj.2016.154
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Environmental Proactivity and Its Determinants in the Hotel Industry

Abstract: The economic literature provides ample evidence that tourism makes intensive use of land both as a product and as a production factor. However, what is now known as mass tourism was developed in a setting in which respect for the environment among businesses and consumers was conspicuous by its absence. This situation has recently changed as consumers increasingly demand sustainable tourism products and require companies to respect specific environmental commitments. How companies manage this new situation wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…According to the results below, five- and four-star hotels are the establishments that most often engage in sustainability communication. This finding is in line with the evidence reported in previous studies (Sánchez-Ollero et al , 2016; Al-Aomar and Hussain, 2017) conducted in other locations, thereby confirming that this tendency is also valid for hotels located in tourist destinations dependent on air transportation.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…According to the results below, five- and four-star hotels are the establishments that most often engage in sustainability communication. This finding is in line with the evidence reported in previous studies (Sánchez-Ollero et al , 2016; Al-Aomar and Hussain, 2017) conducted in other locations, thereby confirming that this tendency is also valid for hotels located in tourist destinations dependent on air transportation.…”
Section: Resultssupporting
confidence: 92%
“…Studies conducted in different geographic locations by Sánchez-Ollero et al (2016) and Al-Aomar and Hussain (2017) found evidence that higher star-rated hotels such as four and five-star hotels are more environmentally proactive. These facilities implement more sustainable practices than lower star-rated hotels do.…”
Section: Sustainability In the Hospitality Sectormentioning
confidence: 99%
“…Thus, communication efforts aimed at highlighting the ethical and social behaviour of organizations have a positive influence on the perceived quality of tourism products and the intention to purchase. In the case of Spain [48] and specifically in Andalusia, some case studies show how certain quality standards (obtained through external certifications to companies) help improve the hotel's productivity [11].…”
Section: Methodsmentioning
confidence: 99%
“…As Gligor-Cimpoieru et al [10] pointed out, most studies in this field are limited to environmental issues, and tend to neglect the social and cultural variables of CSR. Thus, it has often been pointed out that tourism makes intensive use of the environment, which is a de facto indispensable element in the tourism product [5,[11][12][13]. Although this view is generally true, not all tourism activities or all tourism segments have such a direct relationship with the environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is found that the marketing strategies applied by the units in the hotel industry remain the main lifeline that helps them stay in the market. It is already noticeable that consumers are increasingly demanding sustainable tourism products and requiring companies to comply with specific environmental commitments (Sanchez-Ollero, Cappa, Febrero-Panos, 2016). Thus, hotels are increasingly considering sustainability issues in their business models and strategies (Sakshi et al, 2020).…”
Section: Review Of the Scientific Literaturementioning
confidence: 99%